دور ادارة المعرفة في تعزيز الرضا الوظيفي – دراسة حالة مديرية التربية لولاية بسكرة - خوني, رابح; شنوفي, نوال (جامعة الوادي- University of Eloued, 2017)
This study dealt with the role of knowledge management in enhancing job satisfaction among the staff of the Education Directorate of Biskra State. The aim of this study was to identify the role of knowledge management in enhancing job satisfaction in the Directorate. The questionnaire was used as a data collection tool The number of questionnaires valid for the46 resolution analysis to be analyzed using the19 spssv statistical program. The study concluded that the knowledge management variable was76.60% of the changes in job satisfaction. Therefore, this study recommended the need to provide more mechanisms The effectiveness of more knowledge management in the Directorate to free up the creative energies of employees and contribute to the advancement of work
مقال
Keywords: knowledge, knowledge management, job satisfaction